RELIGIOUS DIMENSION OF TURKEY’S POLICY IN AJARIA AND THE GEORGIAN ORTHODOX CHURCH - IVANOV, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2011)
The official atheism of Soviet times prevented any abuse of religion for political reasons; perestroika opened the gates; and as soon as the Soviet Union fell apart, its neighbors, Turkey among them, had the opportunity to put pressure on the post-Soviet expanse. The Turkish political community, which promptly recognized the Soviet Union’s disintegration as a chance to establish Turkey’s domination in neighboring post-Soviet regions, was euphoric. “The collapse of the Soviet Union and the emergence of new Turkic-Muslim republics opened up a chain of possibilities for Turkey to play an important role in the Caucasus and in Central Asia.”1 The religious factor became as important as political, economic, and other factors. Turkish-Georgian relations, which have demonstrated a lot of dynamism in the post-Soviet period (approximately since the mid-1990s when Georgia froze its ethnopolitical conflicts, stabilized its domestic political expanse to a certain extent, and became involved in large-scale energy-communication projects), have not always been that good. The still unsettled and controversial issue of the status of Ajaria with its large Islamic population has been revealing itself during the crises which accompanied the emergence of Georgia’s statehood. Igor Muradyan has written the following on that score: “Between 1992 and 2003 Turkey, concerned about infringement on Ajaria’s rights, interfered in Georgia’s domestic affairs three times.”2 While Aslan Abashidze was in power, Turkey competed with Russia in that part of the Caucasus; as soon as the Russian military base was pulled out of Batumi and relations between Moscow and Tbilisi deteriorated, Turkey became one of the key foreign policy actors in Ajaria. During the Tbilisi-Batumi confrontation triggered by the Rose Revolution, Turkey warned Tbilisi, in so many words, that it was closely following the slightest shifts in the border regions. On 17 March, 2004, Ambassador of Turkey to Azerbaijan Unal Chevikoz declared that, under the Treaty of Kars of 1921, Ankara could move its troops into Ajaria in the event of a crisis. In this way, Turkish diplomats responded to the statement Georgian Ambassador to Russia Konstantine Kemularia made on 16 March to the effect that the Treaty of Kars, under which Batumi was transferred to Georgia, had become null and void.3